Secondary infection by Cryptococcus spp. in HIV-negative patients in the context of Covid-19 - Norberg, Antonio Neres; Norberg, Paulo Roberto Blanco Moreira; Manhães, Fernanda Castro; Ramos, Fabiana Pereira Costa; Mangiavacchi, Bianca Magnelli; Faial , Lígia Cordeiro Matos; Borges, Thaís Rigueti Brasil; Dias, Vinícius Evangelista; Filho, Renato Mataveli Ferreira; Colete, Claudia Caixeta Franco Andrade (Seven Editora, 2023)
Cryptococcosis is an infectious disease with worldwide distribution caused by fungi of the genus Cryptococcus, especially by the species  C. neoformans and C. gattii. Cryptococcus infections begin with the  inhalation of fungal particles that reach the lungs and can spread through hematogenous, especially in hosts with deficiencies in the cellular immune system. The acute respiratory syndrome in COVID-19 promotes a decrease in the efficiency of the immune system, either due to exhaustion resulting from the exacerbated response or due to immunosuppression in treatment with corticosteroids to contain the cytokine cascade in COVID-19, facilitating the appearance of opportunistic fungal infections in patients who develop severe cases of the virus due to SARS-CoV-2. The objective of this research is to conduct a review of clinical cases of cryptococcosis in co-infection with SARS-CoV-2 or the appearance of this mycosis in the post-COVID-19 convalescence period in HIV-uninfected individuals, analyzing the risk factors and circumstances associated with the relationship between cryptococcosis and COVID-19. Although cryptococcosis is a relatively rare infection among patients with COVID-19 and in the convalescence period of the disease, this opportunistic mycosis may be responsible for a mortality rate that is considered high (greater than 55%). Susceptibility to Cryptococcus spp. infection in the context of COVID-19 disease and treatment is strongly associated with corticosteroid use and pre-existing multiple comorbidities. It is not possible to determine the degree to which cryptococcosis is responsible for mortality in co-infection or infection during the COVID-19 convalescence period. The development of secondary infection by Cryptococcus spp. is indicative of a poor prognosis for the patient. DOI:https://doi.org/10.56238/interdiinovationscrese-031